The Economic Dimension of Social Trust - Mularska-Kucharek, Monika; Brzeziński, Kamil (European Spatial Research and Policy, 2017)
Social trust is increasingly seen as a non-economic determinant of economic development. Its positive impact on the economic sphere of social life, proven by numerous studies, is an incentive for new research initiatives examining the social trust level, since the results may be vital for the local policy-making. The main aim of the article is to study the relationships between social trust and the economic development. To accomplish this goal, a social trust indicator and an economic ranking list for the researched units were created. The statistical analyses performed demonstrated a statistically significant correlation between the examined phenomena and proved that the highest developmental level is a characteristic feature of the districts with a high level of social trust. This conforms the claims of Polish and international scholars who see trust as a non-economic determinant of economic development.